Bone Tissue Changes In The Background Of "Activation Of The Immune System" During Orthodontic Treatment And Tskaltubo Water Hormesis - Adamia, Jaba; Nikolaishvili, Marine; Mosemghdvlishvili, Nato (European Scientific Journal, ESJ, 2022)
The use of Tskaltubo radon-containing water in orthodontics will help to improve mineral metabolism, balance between osteoresorption and bone formation phases, and reduce the intensity of osteoclastogenesis. The use of Tskaltubo radon-containing mineral water in orthodontics in comparison with the traditional protocol treatment causes a statistically significant change in the reduction of activators of resorption processes in blood plasma, increase in the level of marker of new bone formation (acid-alkaline phosphatase), as well as osteochondrosis. In particular, a decrease in the sRANKL / OPG ratio and, consequently, a decrease in the level of osteoblastogenesis inhibitor produced by osteoclasts - sclerostin, which is produced by osteoclasts. All these processes already lead to the normalization of bone mineralization, which already has a positive effect on the processes of osteointegration, which other authors note even in the use of very small doses of radiation (hormesis). We have developed an algorithmic method for the diagnosis of patients with chronic generalized periodontitis and the rapid recovery of new bone tissue in the case of orthodontic treatment and the reduction of inflammatory processes over a long period of time.